A Java Multithread Audio Acquisition for Real Time Audio Surveillance - Dadula, C.; Dadios, E. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper presents a real time audio acquisition using a personal computer and multiple USB microphones. When audio stream is available, audio processing techniques can be added to make a real time audio surveillance. The output of this work can be used in audio processing techniques that require audio signals from multiple microphones like source localization and source separation. The designed algorithm implements Java threads and Java sound API (Applications Programming Interface ). Two to five microphone threads were run for about 1 second. Each setup was run for 5 trials. The 2-, 3-, and 4-microphone setup provided a promising result for a given hardware specification. The maximum difference for 2- microphone setup was 939 samples or 117 milliseconds duration. For 3-microphone setup, the maximum difference was 1109 samples or 138 milliseconds duration but the two-microphone setup got equal number of samples for about 60% of the trials. For 4-microphone set-up, the maximum number of difference was 1024 samples or about 128 milliseconds but 3 microphones3 microphones got equal number of samples for about 40% of the trials. The 5-microphone setup demonstrated that system resources cannot support that much number of microphones because the one microphone got a very low number of samples compared to other 4 microphones.